Археологічні дослідження городища Тягинка: деякі результати та завдання - Біляєва, С.О. (Археологія і давня історія України, 2019)
Статтю присвячено результатам археологічних досліджень південної ділянки Литовсько-Руського кордону з Золотоординськими володіннями. The article is devoted to the results of the archaeological investigations of the south part of the Lithuanian- Russ frontiers with the Golden Horde possessions. The place of excavation the fortress Tiagin and settlement of the city type nearby it. The fortress was built by prince Vitovt at the end of XIV — at the beginning of XVth century.Besides of fortification there was a very important custom, known from written records. The first works on this monument were provided in 1914 y, by V. I. Goskevich. Then, some archeologists have been working there, but such monument needed in the special attention and long time excavation. In the course of our investigation in the season of 2016—2018 the very interesting results were obtained. For the first time the artifacts of Lithuanian material culture were found. There were bracelet, and decorative details for leather bags. Besides of it, silver, bronze and copper coins of the end of the XIV — of the first quarter of the XVth century were found also. The most of them were Tatar’s coins, and one — Polish. It support the important place of international trade and integration process in the culture of this period from North to south of Europe.